Local and long-range GABAergic circuits in hippocampal area CA1 and their link to Alzheimer’s disease - Hernández-Frausto, Melissa; Bilash, Olesia M.; Masurkar, Arjun V.; Basu, Jayeeta (Frontiers in Neural Circuits, 2023)
GABAergic inhibitory neurons are the principal source of inhibition in the brain. Traditionally, their role in maintaining the balance of excitation-inhibition has been emphasized. Beyond homeostatic functions, recent circuit mapping and functional manipulation studies have revealed a wide range of specific roles that GABAergic circuits play in dynamically tilting excitation-inhibition coupling across spatio-temporal scales. These include the gating of compartment- and input-specific signaling, gain modulation, shaping input-output functions and synaptic plasticity, signal-to-noise contrast generation, defining temporal windows for integration and rate codes, organization of neural assemblies, coordinating inter-regional synchrony. GABAergic circuits are thus instrumental in controlling single-neuron computations and behaviorally-linked network activity. The activity dependent modulation of sensory and mnemonic information processing by GABAergic circuits is pivotal for the formation and maintenance of episodic memories in the hippocampus. Here, we present an overview of the local and long-range GABAergic circuits that modulate the dynamics of excitation-inhibition and disinhibition in, the main output area of the hippocampus, CA1, which is crucial for episodic memory. Specifically, we link recent findings pertaining to GABAergic neuron molecular markers, electrophysiological properties, and synaptic wiring with their function at the circuit level. Lastly, given that area CA1 is particularly impaired during early stages of Alzheimer’s Disease, we emphasize how these GABAergic circuits may contribute to and be involved in the pathophysiology.